2021
DOI: 10.1021/acs.jpcb.1c03899
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Frontal Polymerization and Instabilities with Phase-Changing Microparticles

Abstract: Recently presented as a rapid and eco-friendly manufacturing method for thermoset polymers and composites, frontal polymerization (FP) experiences thermo-chemical instabilities under certain conditions, leading to visible patterns and spatially dependent material properties. Through numerical analyses and experiments, we demonstrate how the front velocity, temperature, and instability in the frontal polymerization of cyclooctadiene are affected by the presence of poly(caprolactone) microparticles homogeneously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…Systems employing FROMP have heavily employed DCPD or norbornene derivatives as the monomer of choice (refs , , , , , , , , , , , ). As stated previously, the heat released by polymerization (Δ H p ) dictates the feasibility toward frontal application; as a catalytic process, the total quantity of heat released in ROMP depends only on the monomer itself, assuming that the reaction reaches completion.…”
Section: Chemistries Of Existing Frontal Polymerization Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…Systems employing FROMP have heavily employed DCPD or norbornene derivatives as the monomer of choice (refs , , , , , , , , , , , ). As stated previously, the heat released by polymerization (Δ H p ) dictates the feasibility toward frontal application; as a catalytic process, the total quantity of heat released in ROMP depends only on the monomer itself, assuming that the reaction reaches completion.…”
Section: Chemistries Of Existing Frontal Polymerization Systemsmentioning
confidence: 99%
“…Pattern formation in FROMP may also occur through localized disruption of thermal or mass transport. Recent work from Gao et al , demonstrated that the inclusion of poly­(caprolactone) microparticles in COD or DCPD resins introduces bias into the introduces periodic features in the temperature and velocity profiles of the front. During polymerization, the microparticles undergo an endothermic solid to liquid phase change that redirects thermal energy away from the reaction front.…”
Section: Applications Of Frontal Polymerizationmentioning
confidence: 99%
“…The FP-based fabrication of thin layers with thickness down to ∼100 μm on a thermally insulating substrate has been achieved recently with reduced volatile organics emission and controllable initiation of curing, which further broadens the application of FP to the manufacturing of thin coatings. , Because the FP-based manufacturing of thin layers is characterized by a reduced availability of reaction heat, the thermal diffusion into the substrate plays a key role in this process . Therefore, leveraging the competition between the heat generated by the reaction and the thermal transport enables the tuning of key features that influence the efficiency and feasibility of FP, that is, the front shape, velocity, and temperature. , Moreover, thermochemical instabilities emerge at a critical reaction–thermal transport power balance, potentially resulting in polymeric parts with complex geometries and heterogeneous properties . A recent numerical study has reported that the resin layer thickness controls the front dynamics and determines its existence subject to convective heat loss .…”
Section: Introductionmentioning
confidence: 99%
“…Pattern formation in FROMP may also occur through localized disruption of thermal or mass transport. Recent work from Gao et al 153,154 demonstrated that the inclusion of poly(caprolactone) microparticles in COD or DCPD resins introduces bias into the introduces periodic features in the temperature and velocity profiles of the front. During polymerization, the microparticles undergo an endothermic solid to liquid phase change that redirects thermal energy away from the reaction front.…”
Section: Instability Driven Spontaneous Patterningmentioning
confidence: 99%